Salvadoran imaginaries : mediated identities and cultures of consumption - Rivas, Cecilia M., 1978- (Rutgers University Press, 2014)
Accessible and beautifully written, Rivas examines how El Salvador's post-war identity has been transformed by communication technologies, journalistic narratives of migratory experiences, and the complex relationships between private and public spaces of consumption and belonging. This book shows how seemingly disparate sites of experience and representation-call centers, newspapers, shopping malls, and literature-can reveal the complicated process of a nation reinventing itself.
Keywords: Salvadoran Americans -- Social conditions.; El Salvador -- Emigration and immigration.; United States -- Emigration and immigration.; Transnationalism.; Américains d'origine salvadorienne -- Conditions sociales.; Transnationalisme.; États-Unis -- Émigration et immigration.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; SOCIAL SCIENCE -- Ethnic Studies -- Hispanic American Studies.; Emigration and immigration; Transnationalism; El Salvador; United States